Computational inference and control of quality in multimedia services : doctoral thesis accepted by Eindhoven University of Technology, the Netherlands /: doctoral thesis accepted by Eindhoven University of Technology, the Netherlands. ([2015]) - Menkovski, Vlado
No abstract available